Sources of resistance to tobacco streak virus in Wild Arachis (Fabaceae: Papilionoidae) Germplasm - Kalyani, G.; Reddy, A.S.; Kumar, P. Lava; Rao, R.V.D.J.P.; Aruna, R.; Waliyar, Farid; Nigam, S.N. (Scientific Societies, 2007)
Stem necrosis disease caused by Tobacco streak virus (TSV), first recognized in 2000, has emerged as a potential threat to peanut (Arachis hypogaea) in southern states of India. The virus induces severe necrosis of shoots leading to death of the plant, and plants that survive are malformed, with severe reduction in pod yield. All the currently grown peanut cultivars in India are highly susceptible to the virus. Therefore, wild relatives of peanut were evaluated to identify potential sources of resistance to TSV infection. In all, 56 germplasm accessions from 20 wild Arachis spp. in four sections (Arachis, Erectoides, Procumbente, and Rhizomatosae), along with susceptible peanut cultivars (JL 24 and K 1375), were evaluated for resistance to TSV under greenhouse conditions using mechanical sap inoculations. Systemic virus infection, determined by enzyme-linked immunosorbent assay (ELISA), in the test accessions ranged between 0 and 100%. Twenty-four accessions in section Arachis that had 0 to 35% systemically infected plants were retested, and systemic infection was not detected in eight of these accessions in repeated trials in the greenhouse. These are International Crops Research Institute for the Semi-Arid Tropics groundnut (ICG) accession nos. 8139, 8195, 8200, 8203, 8205, and 11550 belonging to A. duranensis; ICG 8144 belonging to A. villosa; and ICG 13210 belonging to A. stenosperma. Even though the resistant accessions had 0 to 100% TSV infection in inoculated leaves, TSV was not detected in the subsequently emerged leaves. This is the first report of TSV resistance in Arachis spp. The eight TSV resistant accessions are cross compatible with A. hypogaea for utilization in breeding for stem necrosis disease resistance.